2018
DOI: 10.1002/bjs.11009
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of shared decision-making in surgery

Abstract: BackgroundMultiple treatment options are generally available for most diseases. Shared decision‐making (SDM) helps patients and physicians choose the treatment option that best fits a patient's preferences. This review aimed to assess the extent to which SDM is applied during surgical consultations, and the metrics used to measure SDM and SDM‐related outcomes.MethodsThis was a systematic review of observational studies and clinical trials that measured SDM during consultations in which surgery was a treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
87
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(94 citation statements)
references
References 60 publications
1
87
0
1
Order By: Relevance
“…This requires cooperation and activation of both clinicians and patients. Despite being so heavily embraced by scientific scholars and policymakers, formal implementation of SDM in practice has proven to be challenging . One key barrier seems to be the perceived time needed to practice SDM, addressing both risk communication and clarification of patients' values .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…This requires cooperation and activation of both clinicians and patients. Despite being so heavily embraced by scientific scholars and policymakers, formal implementation of SDM in practice has proven to be challenging . One key barrier seems to be the perceived time needed to practice SDM, addressing both risk communication and clarification of patients' values .…”
Section: Introductionmentioning
confidence: 99%
“…One key barrier seems to be the perceived time needed to practice SDM, addressing both risk communication and clarification of patients' values . Although clinicians generally support SDM, they are also often hesitant to practice it and often revert to a more authoritarian conversational model …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, a current project (26) is underway to develop a core outcome set to improve reporting of outcomes and consent processes. A systematic review to identify features of SDM in surgery conducted by de Mik et al (27) showed that surgeons and patients both recognized SDM, although SDM in surgery is in its infancy. Therefore, strategies to effectively practice and assess SDM in surgery are particularly important.…”
Section: Research Hotspots and Frontiersmentioning
confidence: 99%